1997
DOI: 10.1161/01.str.28.3.665
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of In Vivo Carotid Intima-Media Thickness Measurements

Abstract: We conclude that a consensus concerning the assessment of IMT is urgently needed. Variability of IMT measurements is lowest when determining the mean thickness in the common carotid artery in different directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
219
4
12

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(252 citation statements)
references
References 48 publications
17
219
4
12
Order By: Relevance
“…The effect of semi-automated edge detection on the extent of reduction in measurement variability depends on the contribution of sonographers and readers to the total variability. A number of studies have indicated that differences between sonographers have a relatively larger effect on the CIMT measurements than differences between readers [15][16][17]. Indeed, reproducibility results from a study with images that were read using semi-automated edge detection were similar to those reported from other studies in which CIMT reading was performed manually [16].…”
Section: Introductionsupporting
confidence: 64%
“…The effect of semi-automated edge detection on the extent of reduction in measurement variability depends on the contribution of sonographers and readers to the total variability. A number of studies have indicated that differences between sonographers have a relatively larger effect on the CIMT measurements than differences between readers [15][16][17]. Indeed, reproducibility results from a study with images that were read using semi-automated edge detection were similar to those reported from other studies in which CIMT reading was performed manually [16].…”
Section: Introductionsupporting
confidence: 64%
“…As expected, the reproducibility of the EXP reader was better than that of the NOV reader; however, CV for the measurements using BDP were excellent and comparable with other studies. 9,14,15 Measurements by both NOV and EXP readers correlated strongly with those of the REF laboratory with minimal systematic bias, and bioequivalence was demonstrated. BlandAltman plots and linear regression models for mean and maximum CIMT values successfully illustrate the striking similarity between the readers using BDP and the REF laboratory, and high intrareader repeatability.…”
Section: Discussionmentioning
confidence: 72%
“…We used carotidfemoral PWV and CIMT as surrogate measures for structural and functional abnormality of the arterial wall as they have shown to be valid and reproducible methods that are simple and non-invasive. 22,23 A major concern in studies that relate the biomarkers to disease is confounding by a third variable through unknown mechanisms. Consistent with previous evidence, our finding showed that most of the established cardiovascular risk factors are determinants of aortic PWV and CIMT.…”
Section: Discussionmentioning
confidence: 99%